Cyclophilin A is an important mediator of platelet function by regulating integrin αIIbβ3 bidirectional signalling - Wang, Lian; Soe, Nwe Nwe; Sowden, Mark; Xu, Yingqian; Modjeski, Kristina; Baskaran, Padmamalini; Kim, Yeonghwan; Smolock, Elaine M.; Morrell, Craig N.; Berk, Bradford C. (Thrombosis and Haemostasis, 2014)
Cyclophilin A (CyPA) is an important mediator in cardiovascular diseases. It possesses peptidyl-prolyl cis-trans isomerase activity (PPIase) and chaperone functions, which regulate protein folding, intracellular trafficking and reactive oxygen species (ROS) production. Platelet glycoprotein receptor αIIbβ3 integrin activation is the common pathway for platelet activation. It was our objective to understand the mechanism by which CyPA-regulates αIIbβ3 activation in platelets. Mice deficient for CyPA (CyPA−/−) had prolonged tail bleeding time compared to wild-type (WT) controls despite equivalent platelet numbers. In vitro studies revealed that CyPA−/− platelets exhibited dramatically decreased thrombin-induced platelet aggregation. In vivo, formation of occlusive thrombi following FeCl3 injury was also significantly impaired in CyPA−/− mice compared with WT-controls. Furthermore, CyPA deficiency inhibited flow-induced thrombus formation in vitro. Flow cytometry demonstrated that thrombin-induced ROS production and αIIbβ3 activation were reduced in CyPA−/− platelets. Coimmunoprecipitation studies showed ROS-dependent increased association of CyPA and αIIbβ3. This association was dependent upon the PPIase activity of CyPA. Significantly, fibrinogen-platelet binding, platelet spreading and cytoskeleton reorganisation were also altered in CyPA−/− platelets. Moreover, CyPA deficiency prevented thrombin-induced αIIbβ3 and cytoskeleton association. In conclusion, CyPA is an important mediator in platelet function by regulation of αIIbβ3 bidirectional signalling through increased ROS production and facilitating interaction between αIIbβ3 and the cell cytoskeleton.
Keywords: Platelets; integrin αIIbβ3; cyclophilin A; cell cytoskeleton; thrombin